Amphoteric polycarboxylate superplasticizers with enhanced clay tolerance: Preparation, performance and mechanism. (20th August 2020) - Tang, Xinde; Zhao, Chunli; Yang, Yueqing; Dong, Fuying; Lu, Xiao
Graphical abstract: Highlights: Three different kinds of amphoteric polycarboxylate (APC) superplasticizers were synthesized. APC displays better dispersion performance than common polycarboxylate ether (PCE) superplasticizers. APC can inhibit the side effects of clay and exhibit enhanced clay tolerance. APC can effectively improve the strength of mortar and concrete. The intercalation effect of APC to clay may be derived from cation exchange, different from that of PCE. Abstract: From the point view of molecular structure design, three different kinds of amphoteric polycarboxylate superplasticizers (APC) by introducing a cationic monomer such as [2-(methacryloyloxy)ethyl]trimethylammonium chloride (DMC), 3-[2-(methacryloyloxy)ethyl]dimethylammonio-propane-1-sulfonate (DMAPS) and acrylamide (AM) were synthesized by free radical polymerization. The functional groups, molecular weights and molecular weight distributions of these superplasticziers were characterized by Fourier transform infrared spectra (FT-IR) and gel permeation chromatography (GPC). The dispersion performance of as-prepared APC were evaluated by the fluidity of cement paste and cement mortar. The results showed that the fluidities of samples mixed with APC were higher than that of the conventional polycarboxylate ether (PCE) superplasticizers, indicating excellent dispersion performance and dispersion retention. The strengths of concrete with APC or PCE were greatly improved compared with that of the standard concrete, and the strengths of samples with APC were superior to that with PCE. By substituting cement with 1 wt% sodium bentonite, the fluidity of the cement pastes with APC was higher than that with PCE1, which can be ascribed to the enhanced clay tolerance of APC. Total organic carbon (TOC), X-ray diffraction (XRD) and thermo gravimetric analysis (TGA) were conducted to study the adaptability of superplasticizers to cement and clay. Adsorption capacity measurement revealed that APC and PCE exhibit selective adsorption on cement and clay and APC exhibited better adaptability to clay than PCE. The interlayer spacing of sodium bentonite increased by 0.2 nm after the adsorption of superplasticizer, without significant difference between APC and PCE. A possible mechanism was proposed that the cationic groups can insert into the interlayer of clay by cation exchange, and the intercalation of PEO side chains was inhibited, which is different from that of PCE.